The Role of Behavioral Economics in Marketing Strategies - Kaur, Rupinder (AG Volumes, 2024)
Today’s competitive business environment has made it increasingly important to comprehend consumer behaviour. It provides invaluable insights into the decision-making process of individuals, as behavioural economics is a combination of economics and psychology. These principles can be employed by marketers to develop strategies that are profoundly resonant with consumers, thereby facilitating engagement and conversions. In this article review the various literature’s study on role of behavioral economics in marketing strategies. It concluded that behavioral economics has significantly influenced marketing by leveraging psychological triggers such as scarcity, social proof, and emotional appeal to shape consumer behavior. Emotionally engaged consumers exhibit greater loyalty, while personalized recommendations from companies like Amazon and Netflix enhance customer retention. Pricing strategies, including anchoring and implicit pricing, manipulate consumer perceptions to drive sales. Social influence and scarcity effects further increase motivation to purchase. However, ethical considerations must be addressed to ensure transparency. By applying behavioral economics principles, firms can create more engaging marketing strategies, strengthen brand loyalty, and enhance consumer decision-making in an increasingly competitive market.